2013
DOI: 10.1586/14787210.2014.856755
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for statins in fungal infections?

Abstract: It has been hypothesized that statins, HMG-CoA reductase inhibitors, may be used to treat fungal infections. Here we review data on antifungal properties of statins, effects on the host inflammatory response as well as available clinical evidence. We conclude that: statins exhibit antifungal properties in vitro although at supraphysiological concentrations; statins appear to have anti-inflammatory effects on host cells in vitro; statins have effects on fungal physiology beyond direct growth inhibition; clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…The first compound, the HMG-CoA reductase inhibitor simvastatin, is a cholesterol-lowering drug for which antifungal activity has been described previously 44 . Both statins and azoles target the ergosterol biosynthesis pathway in C. albicans .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first compound, the HMG-CoA reductase inhibitor simvastatin, is a cholesterol-lowering drug for which antifungal activity has been described previously 44 . Both statins and azoles target the ergosterol biosynthesis pathway in C. albicans .…”
Section: Discussionmentioning
confidence: 99%
“…The potential of statins in systemic antifungal therapy is debated, due to the low concentrations that can be reached in blood. Moreover, the combination of statins with azole antifungals is questionable since azoles are potent inhibitors of CYP enzymes, leading to arrested metabolism of many statins in the liver 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the medication of these patients, several molecules are reported to be associated with altered susceptibility to fungal infections and can influence yeast colonization in this population. 47.6% of the PD patients were on calcium channel blockers therapy, described to have an inhibitory effect on oxidative stress response of Candida albicans [ 11 ]; 57.1% were prescribed with statins, 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase inhibitors, used to lower patients' cholesterol but that also affects ergosterol levels exhibiting antifungal properties [ 12 ]; 71.4% were supplemented with vitamin D known to affect fungal growth in a dose-dependent manner [ 13 ]; and 90.5% had iron supplementation, an essential element for microbial growth and known to influence host susceptibility to C. albicans infections [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…HMG-CoA inhibitors, a class known as statins, are widely used in humans to reduce cholesterol levels. The similarity between human and fungal HMG-CoA has raised interest in the potential of statins as antifungal drugs (Bergman and Björkhem-Bergman, 2013). However a meta analysis of five retrospective studies found no positive effects for the use of statins during fungal infection (Bergman and Björkhem-Bergman, 2013).…”
Section: Hmg-coa Reductase Inhibitorsmentioning
confidence: 99%